Slogans of Top Fast Food Brands : Advertising Appeal and Language - Pung, Wun Chiew; Nurin Nisa', Aminuddin (UNIMAS Publisher, 2023)
Advertisements are an integral part of our life. We see them almost everywhere - billboards, television, magazines, the Internet, social media, etc. However, some advertisements seem to catch our attention better and stay in our memory longer than others. Additionally, we are able to recognise specific brand phrases more quickly than those of other companies, such as the well-known Nike motto, “Just do it.” How can advertisers persuade consumers to purchase their product or service?